2012
DOI: 10.1017/s1368980011003338
|View full text |Cite
|
Sign up to set email alerts
|

The making of a nutrition professional: the Association for Nutrition register

Abstract: Objective: Nutritionists in the UK are at the start of an exciting time of professional development. The establishment of the Association for Nutrition in 2010 has presented an opportunity to review, revitalize and expand the UK Voluntary Register of Nutritionists. In the UK and elsewhere, there is a need for a specialist register of nutritionists with title protection as a public safeguard. Design: The new structure will base professional registration on demonstration of knowledge and application in five core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…It has a set of standards for registration as a nutritionist and for the accreditation of courses. The course accreditation criteria cover core knowledge and skills for courses and the registration criteria cover core knowledge, skills and competencies for practicing nutritionists ( 21 ) . An important component of the latter is that it includes information on institutional quality assurance processes, staffing capacity and facilities ( 20 , 22 ) .…”
Section: Current Nutrition Training Opportunities In Sub-saharan Africamentioning
confidence: 99%
“…It has a set of standards for registration as a nutritionist and for the accreditation of courses. The course accreditation criteria cover core knowledge and skills for courses and the registration criteria cover core knowledge, skills and competencies for practicing nutritionists ( 21 ) . An important component of the latter is that it includes information on institutional quality assurance processes, staffing capacity and facilities ( 20 , 22 ) .…”
Section: Current Nutrition Training Opportunities In Sub-saharan Africamentioning
confidence: 99%
“…Relevant competencies: CC3c, CC3e, CC3f The participants (2)(3)(4)(5)(6)(7)(8) suggested that organising and structuring their lives was important to ensure adherence (nine references) and that when that structure was challenged, adherence became difficult. A lack of structure, organisation and time management led to previous failures for some:…”
Section: Self-managementmentioning
confidence: 99%
“…Some participants revealed that stressful life events led to binge eating in the absence of sufficient coping mechanisms and comfort eating was problem for some. Social situations were revealed unanimously to threaten consistency (1)(2)(3)(4)(5)(6)(7)(8) and the following examples were described as coping mechanisms for such occasions: driving instead of drinking, limiting food choices, flexible restraint and increasing exercise:…”
Section: Relevant Competencies: Cc3c Cc3fmentioning
confidence: 99%
See 1 more Smart Citation
“…We have included two more workforce development papers in this issue. The first one, by Janet Cade and colleagues, looks at the British Register of Nutritionists, which is one of the very few systematic attempts to register nutritionists, and in this case includes public health nutritionists ( 7 ) . The paper by Kandelwal and co-workers maps nutrition teaching and training initiatives in India, indicating the gap in public health nutrition training ( 8 ) .…”
mentioning
confidence: 99%